How anthocyanin biosynthesis affects nutritional value and anti-inflammatory effect of black rice. (September 2021) - Zhao, Mingchao; Huang, Chunhua; Mao, Qinquan; Zhou, Zaihui; Xiang, Yuanhang; Zhang, Qinglu; Lin, Yongjun; Chen, Hao
Abstract: Black rice is reportedly more nutritious than common white rice and has specific health-promoting effects. To accurately evaluate nutritious and functional differences between black rice and white rice, we generated a homogenous mutant line with anthocyanin-deficient mutation (AM22) from the black rice variety Heishuai. Compositional and metabolomic analyses identified significant content differences in six amino acids, vitamin B2, copper, manganese, and 257 secondary metabolites between AM22 and Heishuai. Meanwhile, the result from mouse ear edema model suggested that anti-inflammatory effect of AM22 was significantly attenuated compared with Heishuai. Transcriptional analysis revealed that the anti-inflammatory effects elicited by black rice was coupled with expression alterations of 32 inflammation-associated genes in mice and four of them ( Il-1b, Il-17ra, Icam1, and Ptgs2 ) were confirmed by western blotting assay. Our results provide insights how anthocyanin biosynthesis affects the nutritional and functional values of black rice. Graphical abstract: Image 1 Highlights: AM22 is a homogenous mutant with anthocyanin mutation derived from black rice Heishuai. AM22 contains less vitamin B2 and flavonoids compared with Heishuai. AM22 exhibited the attenuated inflammation inhibitory effect compared with Heishuai.